ANALYTICAL TOOLS IN ENSURING THE CONVERGENCE OF ACCOUNTING AND INFORMATION SYSTEMS - Kraievskyi Volodymyr Mykolaiovych; Okhrimenko Ihor Vitaliiovych; Skoryk Maryna Olehivna; Lysiuk Alona Vasylivna; Hmyrya Viktoriia Petrivna (Scientific Journal of Pedagogy and Economics, 2021)
The accounting system by virtue of the subject and method of the latter, is able to model a picture of the real activities of the enterprise, to provide information about the financial condition of the enterprise, its financial results and more. Thus, it is obvious that accounting, as an accounting system, provides an opportunity to form objective information about the business entity and provides users with useful information about the real model of financial and economic activities of economic entities at the micro-, meso- and macro levels. However, it is obvious that the needs of users of financial statements differ. Accounting systems are the result of user information requests. The perspective of the accounting system depends on the requirements of users for accounting information. The dialectic of interests is a complex and multifaceted category. At the present stage of socio-economic development, researching economic interests, we should be guided not by the principle of their rigid hierarchy «from general to individual» or vice versa, but to seek attempts to harmonize them at all levels of socio-economic policy. Economic interests determine the direction and motivation of economic entities, which is aimed at meeting their needs. Here we have to take into account that these interests can be considered both at the national level (macroeconomic) and at the level of an individual business entity (micro level). Achieving the goal of all subjects of socio-economic life at different levels is realized in the process of making management decisions based on relevant economic information.